Microbiological and Sensory Profile of Collagen Supplemented Milk with Pretreatment and Pulsed Electric Field Pasteurization Process - Esfandiar, Wildan Naufal; Yulistiani, Ratna; Dany Priyanto, Anugerah; Agung Wicaksono, Luqman; Safitri, Serly; Dinar Dhiny, Almira (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Collagen-supplemented milk products are susceptible to damage due to high-temperature processing Pulsed Electric Field (PEF) pasteurization is carried out with a pretreatment temperature of <65oC to maintain quality. This study aims to determine the total microbe, the level of microbial decline and the intensity of the sensory profile of milk supplemented with collagen by pretreatment in the PEF pasteurization process. This study used a completely randomized design with a factorial pattern of 2 factors and 3 replications, the first factor was the pretreatment temperature (30, 45 and 60oC), and the second factor was the pretreatment time (10, 20, 30 minutes) which was then pasteurized using the PEF method with a voltage of 15 kv/cm for 120 seconds. Furthermore, these 9 treatments were compared with PEF pasteurized milk without pretreatment and Low Temperature Long Time / LTLT pasteurized milk (pasteurized at 65oC for 30 minutes). The results showed that pretreatment with a temperature of 60oC for 20 and 30 minutes resulted in a total microbial count of 3.406±0.19 CFU/mL and 3.395±0.146 log CFU/mL, respectively. The average total microbe of milk supplemented with collagen in the combination of PEF pasteurization with pretreatment is smaller than the pretreatment process alone with a value below the SNI standard so it is safe for consumption. The average microbial decrease was 2.88 log cycles and was not significantly different (P<0.05) with LTLT thermal pasteurization. The results of the sensory profile intensity test showed that the pretreatment with a temperature of 60oC for 10, 20 and 30 minutes had a sensory profile value that was closest to LTLT pasteurization on the attributes of fishy aroma, milk aroma, and milk taste.